DESIGN, ANALYSIS & WEIGHT OPTIMIZATION OF DRIVE SHAFT BY USING COMPOSITE MATERIAL - Prof. S. M. Bandgar; Mr. Shahrukh Mulla; Yashpal Khedkar (International Journal of Innovations in Engineering Research and Technology, 2022)
The aim of our project work is to replace the metallic propeller shaft of automotive by composite propeller shaft. The requirement of this modification is to increase the efficiency of the power transmission by reducing the weight of the propeller shaft. We are intend to analyse through catia / solid work simulation.